2010
DOI: 10.2164/jandrol.110.011353
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Azoospermia and Cryptozoospermia--Fresh/Frozen Testicular or Ejaculate Sperm for Better IVF Outcome?

Abstract: Men diagnosed as having azoospermia occasionally have a few mature sperm cells in other ejaculates. Other men may have constant, yet very low quality and quantity of sperm cells in their ejaculates, resulting in poor intracytoplasmic sperm injection (ICSI) outcome. It has not been conclusively established which source of sperm cells is preferable for ICSI when both ejaculate and testicular (fresh or frozen) sperm cells are available. It is also unclear whether there is any advantage of fresh over frozen sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 16 publications
2
79
0
2
Order By: Relevance
“…As a result of these observations, a number of investigators have now compared ICSI outcomes with testicular vs. ejaculated spermatozoa in men with cryptozoospermia. To date, several studies have reported higher ICSI pregnancy rates using testicular vs. ejaculated spermatozoa (in most series, ejaculated spermatozoa were used in the initial ICSI cycles) in men with cryptozoospermia (Bendikson et al, 2008;Hauser et al, 2011;Ben-Ami et al, 2013). These clinical findings support experimental observations demonstrating that in animals with impaired spermatogenesis, post-testicular spermatozoa have poorer chromatin integrity than testicular spermatozoa (Suganuma et al, 2005).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…As a result of these observations, a number of investigators have now compared ICSI outcomes with testicular vs. ejaculated spermatozoa in men with cryptozoospermia. To date, several studies have reported higher ICSI pregnancy rates using testicular vs. ejaculated spermatozoa (in most series, ejaculated spermatozoa were used in the initial ICSI cycles) in men with cryptozoospermia (Bendikson et al, 2008;Hauser et al, 2011;Ben-Ami et al, 2013). These clinical findings support experimental observations demonstrating that in animals with impaired spermatogenesis, post-testicular spermatozoa have poorer chromatin integrity than testicular spermatozoa (Suganuma et al, 2005).…”
Section: Discussionsupporting
confidence: 54%
“…All the couples were told of the potential risks of TESA and micro-TESE (bleeding, infection, pain, hypogonadism, irreversible testicular dysfunction). Patients were told that cryptozoospermia is not an absolute but rather a relative indication for sperm retrieval based on the understanding that (i) in some instances the number and/or quality of the ejaculated spermatozoa will not be adequate for ICSI and (ii) couples with cryptozoospermia have relatively poor ICSI pregnancy rates (using ejaculated spermatozoa) (Bendikson et al, 2008;Hauser et al, 2011).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Testicular sperm extraction (TESE) is a method of surgically retrieving sperm from the testis in patients with azoospermia or cryptozoospermia. ICSI using testicular sperm has a higher implantation rate and pregnancy rate than that using ejaculated sperm [112,113]. However, testicular sperm has a significantly higher aneuploidy rate than ejaculated sperm [111].…”
Section: Testicular Sperm Extractionmentioning
confidence: 96%